A ranking for the Vancouver 2010 Winter Olympic Games based on a hyerarchcical Copeland method - Correia Baptista Soares de Mello, J. C.; Carvalho Rosa Bergiante, N. (Advanced Topics in Applied Operations Management, 2012)
In this work we have proposed a study of the results of Vancouver 2010 Olympic Games. We have obtained some interesting results such as countries that have an unbalanced number of medals and take part in modalities that distribute a small number of medals. Another interesting aspect found in this study is the Finland results. In the evaluation, we found that it probably invest in sports based in teams in which the number of medals are smaller than in other modalities and also it had won more silver and bronze medals than gold medals. This result corroborates the findings in Bergiante and Soares de Mello (2010) and helps us to understand some peculiar political sports decisions took by a couple of countries. As a future work suggestion, an interesting proposal is to cluster countries by modalities in order to build others Olympic Rankings [Soares de Mello et al (2009)]. Another option is to explore the economic aspect of these conclusions and develop a model of investment politics in sports for each country.